Effects of coenzyme q10 supplementation on metabolic and reproductive outcomes in obese rats - Gisela Belén Sarrible; María Victoria Bazzano; Caterina Koutsovitis; María Guillermina Bilbao; Rodrigo Hernán Da Cuña; Melanie Neira; Julián Alberto Bartolomé; Evelin Mariel Elia (Journal of Ovarian Research)
Abstract Obesity, a global epidemic, is linked to adverse reproductive outcomes, including infertility and ovulation dysfunction. The cafeteria diet (CAF) serves as an animal model mirroring Western diet habit. Coenzyme Q10 (CoQ10), known for enhancing reproductive outcomes in various pathologies, is not fully understood for its effects on obesity treatment. Here, obesity was modeled using CAF-fed rats to assess CoQ10's impact on metabolic and ovarian disruptions caused by obesity. Wistar rats were divided into control (standard diet) and obese (CAF diet) groups. After 75 days, half of each group received oral CoQ10 (5 mg/kg) for 13 days, while the rest received a vehicle. Animals were euthanized during the estrus phase, and blood and ovaries were collected for analysis. CAF caused increased body weight gain (p < 0.01) associated with hyperglycemia, hypertriglyceridemia, and hypercholesterolemia (p < 0.05). Moreover, it caused a reduction in the number of AMH + follicles (p < 0.001), increasing follicular atresia (p < 0.05) and serum estradiol levels (p < 0.05). Obesity also altered the estrous cycle and reduced the ovulation rate (p < 0.05). CoQ10 administration showed beneficial effects on all ovarian disruptions but had no effect on the metabolic alterations induced by obesity. In summary, CoQ10 could be an additional treatment for obesity-related infertility in patients with normal metabolic profiles. While CoQ10 does not affect metabolic parameters influenced by obesity, crucial for reproductive issues and offspring health, it is recommended as part of a treatment plan that includes a balanced diet and increased physical activity for obese individuals with metabolic alterations seeking pregnancy.